Variation of phytoplankton community structure in Quang Ngai coastal waters during 2015–2019 - Duyen, Huynh Thi Ngoc; Hue, Tran Thi Minh; Van, Tran Thi Le; Luom, Phan Tan; Lam, Nguyen Ngoc; Hai, Doan Nhu (Vietnam Journal of Marine Science and Technology, 2021)
Phytoplankton in coastal waters are important for the evaluation of either biodiversity or environmental impacts because of this highly vulnerable ecosystem. Seasonal and annual changes in the phytoplankton community structure in Quang Ngai waters during the period 2015 to 2019 were analyzed to assess the phytoplankton diversity and reveal possible causes of these changes. A total of 366 phytoplankton taxa belonging to 10 classes were identified throughout this present study. The highest species number was found in 2019 with 295 taxa, followed by those in 2015 (247), 2017 (185), and 2018 (99). The waters of Ly Son transect showed the highest diversity and most stable phytoplankton communities in both dry and rainy seasons, whereas the stations of Quang Ngai coast revealed high variability of the communities. All diversity indices including Margalef, Pielou, Shannon, Simpson did not reflect well differences in average values but a certain degree of variances, indicating possible environmental impacts. During the study time, there were blooms of certain diatom species including Skeletonema spp. in 2015 and Pseudo-nitzschia spp. in 2019. Analysis of a diatoms index, Centric/Pennate ratio, indicated that the waters were in eutrophic status with a decreasing trend from the coast area to Ly Son island in 2015 and 2019. This research built up fundamental data on phytoplankton communities for Quang Ngai province. The Centric/Pennate diatom index and diversity would be used as indicators for environmental changes and their values provided warning of eutrophication in this coastal waters including the water surrounding Ly Son island.